Digital Governance and Community Participation in Urban Public Service Delivery - Mehra, Rohan (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2026)
Digital governance has transformed the interaction between governments and citizens, particularly in urban public service delivery. This study examines how digital platforms influence community participation, transparency, and administrative efficiency in metropolitan contexts. Drawing from interdisciplinary perspectives in sociology, political science, and communication studies, the research explores the role of digital tools in fostering inclusive governance while addressing persistent inequalities in access and digital literacy. The study employs a qualitative-descriptive approach supported by secondary data and case analysis of selected urban governance initiatives. Findings indicate that digital governance enhances responsiveness and citizen engagement when supported by strong institutional frameworks and community outreach programs. However, structural disparities—such as unequal internet access and socio-economic divides—continue to limit participation among marginalized groups. The research highlights the need for policy integration that combines technological innovation with social inclusion strategies. The study contributes to ongoing debates on governance transformation by emphasizing the sociological implications of digital administration and its impact on participatory democracy. Recommendations include strengthening digital literacy programs, ensuring equitable infrastructure, and embedding participatory mechanisms within governance systems.